2022
DOI: 10.47836/pjssh.30.4.25
|View full text |Cite
|
Sign up to set email alerts
|

Developing Conceptual Change Text on the States of Matter and Their Changes for Prospective Elementary School Teachers

Abstract: This research aims to develop a Conceptual Change Text (CCT) for prospective elementary school teachers’ understanding of states of matter and their changes through text to fulfill valid, practical, and effective criteria about the Basic Concepts of Science, henceforth TPK-MP (Teks Perubahan Konseptual Materi dan Perubahannya). This research employs research and development of the 4D model: define, design, develop, and disseminate. The instruments included observation, questionnaire, interview guidelines, vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…The reason for this may be the effects of conceptual change texts in creating conceptual change by making students aware of existing misconceptions and the aspects of these structures that conflict with scientifically accepted knowledge. There are many studies in the literature on conceptual change texts that yielded successful results in conceptual change (Banawi et al, 2022;Chambers & Andre, 1997;Hynd, 2001;Jacobson et al, 2021;Sinatra, 2022;Şahin, Bülbül & Durukan, 2013). For example, Şahin, Bülbül, and Durukan (2013) concluded that conceptual change texts were effective in eliminating students' misconceptions about celestial bodies.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…The reason for this may be the effects of conceptual change texts in creating conceptual change by making students aware of existing misconceptions and the aspects of these structures that conflict with scientifically accepted knowledge. There are many studies in the literature on conceptual change texts that yielded successful results in conceptual change (Banawi et al, 2022;Chambers & Andre, 1997;Hynd, 2001;Jacobson et al, 2021;Sinatra, 2022;Şahin, Bülbül & Durukan, 2013). For example, Şahin, Bülbül, and Durukan (2013) concluded that conceptual change texts were effective in eliminating students' misconceptions about celestial bodies.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…Penilaian autentik ini sangat berperan dalam pembelajaran, salah satunya dalam pembelajaran IPA. Pembelajaran IPA pada tingkat sekolah dasar bertujuan untuk mengembangkan pemahaman peserta didik tentang konsep-konsep sains serta meningkatkan keterampilan peserta didik dalam mengaplikasikan konsep-konsep tersebut dalam kehidupan sehari-hari (Abualrob, 2019;Banawi et al, 2022;Prananda, 2020).…”
Section: Gambar 1 Perbedaan Ranah Kognitif Penilaian Autentik Dengan ...unclassified